THE DEVELOPMENT OF ARTICULATE STORYLINE 360 MEDIA TO EXPLORE HOTS ACCORDING TO BROOKHART ON COMPARISON MATERIAL - Gustiani, Yulita; Madawistama, Sri Tirto (Journal of Authentic Research on Mathematics Education (JARME), 2024)
This study aims to describe the development procedure and test the effectiveness of the Articulate Storyline 360 instructional media on comparison topics, as well as analyze the improvement in students' Higher Order Thinking Skills (HOTS) based on Brookhart’s framework. The research method used is research and development (RD) with the Multimedia Development Life Cycle (MDLC) model, which includes six stages: Concept, Design, Material Collecting, Assembly, Testing, and Distribution. The subjects of the study were students selected purposively. The instruments used included HOTS tests, observation sheets, and questionnaires to measure the effectiveness of the media. The results show that the instructional media developed through the MDLC stages was effective, with a significant increase in students' post-test scores compared to pre-test scores. The media significantly improved students' understanding of the comparison concepts and their HOTS, making it recommended for widespread use in mathematics education to support higher-order thinking development.